2020
DOI: 10.1155/2020/3296192
|View full text |Cite
|
Sign up to set email alerts
|

TRAF6 Promotes Gastric Cancer Cell Self-Renewal, Proliferation, and Migration

Abstract: Gastric cancer is the third most common type of tumor associated with death. TRAF6 belongs to the tumor necrosis factor receptor-associated factor family and has been demonstrated to be involved in tumor progression in various cancers. However, the exact effect of TRAF6 on gastric cancer stem cells has not been extensively studied. In this study, abnormal expression of TRAF6 was found in gastric cancer tissues. Overexpression of TRAF6 enhanced proliferation and migration, and TRAF6 knockdown reversed this phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 45 publications
(50 reference statements)
1
12
0
Order By: Relevance
“…Interestingly, the binding relation between TRAF6 mRNA and METTL3 has been verified in microglia [32] . TRAF6 is a notable oncogene in esophageal squamous cell carcinoma, pancreatic cancer, prostate cancer, nasopharyngeal carcinoma, and gastric cancer [33] , [34] , [35] , [36] , [37] . Moreover, the expression of Vimentin was downregulated and that of E-cadherin was elevated after TRAF6 knockdown in cancer stem cells of squamous cell carcinoma of head and neck [38] , indicating the possible role of TRAF6 in regulating the EMT event.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the binding relation between TRAF6 mRNA and METTL3 has been verified in microglia [32] . TRAF6 is a notable oncogene in esophageal squamous cell carcinoma, pancreatic cancer, prostate cancer, nasopharyngeal carcinoma, and gastric cancer [33] , [34] , [35] , [36] , [37] . Moreover, the expression of Vimentin was downregulated and that of E-cadherin was elevated after TRAF6 knockdown in cancer stem cells of squamous cell carcinoma of head and neck [38] , indicating the possible role of TRAF6 in regulating the EMT event.…”
Section: Discussionmentioning
confidence: 99%
“…Smad2 and Smad3 are phosphorylated by TGF-b1 signals, then form hetero trimeric complexes about Smad4, translocating into the nucleus, activating the expression level of EMT-TFs, and cooperating with these transcription factors to regulate EMTrelated genes (79). In addition, non-Smad pathways are also involved in the TGF-b1-induced EMT process, such as phosphatidylinositol 3-kinase (PI3K)/AKT/mammalian TOR complex 1 (mTORC1), tumor necrosis factor receptorassociated factor 6 (TRAF6)/TGF b-Activated Kinase 1 (TAK1), and Wnt/b-catenin signaling (80)(81)(82).…”
Section: The Emt Processmentioning
confidence: 99%
“…Previous studies have reported that EMT may be related to the stemness of CSCs (25)(26)(27). Therefore, whether RORβ played a role in modulating the metastatic ability of GC cells was investigated.…”
Section: Rorβ Confers Resistance To Emt In Gc Cellsmentioning
confidence: 99%